SOCIAL CAPITAL, ENTREPRENEURIAL CAPABILITIES, AND GOVERNMENT REGULATIONS ON START-UP SUCCESS - Yulianti, Yulianti; Salampessy, Maryam; Akbar, Muhamad; Gustini, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the influence of social capital, entrepreneurial capabilities, and government regulations on start-up success, as well as the moderating roles of entrepreneurial capabilities and government regulations on the relationship between social capital and venture performance. Utilizing a quantitative approach and data collected from 250 early-stage entrepreneurs, structural equation modeling (SEM) was employed to analyze the direct and interaction effects among variables. The findings reveal that social capital, entrepreneurial capabilities, and government regulations each have a significant positive impact on start-up success. Furthermore, entrepreneurial capabilities and government regulations significantly strengthen the positive relationship between social capital and start-up success. These results underscore the importance of not only developing strong social networks but also enhancing entrepreneurial skills and fostering supportive regulatory environments to maximize venture performance. This integrated approach provides valuable insights for entrepreneurs, educators, and policymakers aiming to nurture sustainable start-up ecosystems. Implications for theory and practice, as well as directions for future research, are discussed.